Curcumin analog HO‐3867 triggers apoptotic pathways through activating JNK1/2 signalling in human oral squamous cell carcinoma cells. Issue 8 (21st February 2022) - Chen, Chi‐Wei; Hsieh, Ming‐Ju; Ju, Po‐Chung; Hsieh, Yi‐Hsien; Su, Chun‐Wen; Chen, Yen‐Lin; Yang, Shun‐Fa; Lin, Chiao‐Wen
Abstract: Human oral squamous cell carcinoma (OSCC) is the common head and neck malignancy in the world. While surgery, radiotherapy and chemotherapy are emerging as the standard treatment for OSCC patients, the outcome is limited to the recurrence and side effects. Therefore, patients with OSCC require alternative strategies for treatment. In this study, we aimed to explore the therapeutic effect and the mode of action of the novel curcumin analog, HO‐3867, against human OSCC cells. We analysed the cytotoxicity of HO‐3867 using MTT assay. In vitro mechanic studies were performed to determine whether MAPK pathway is involved in HO‐3867 induced cell apoptosis. As the results, we found HO‐3867 suppressed OSCC cells growth effectively. The flow cytometry data indicate that HO‐3867 induce the sub‐G1 phase. Moreover, we found that HO‐3867 induced cell apoptosis by triggering formation of activated caspase 3, caspase 8, caspase 9 and PARP. After dissecting MAPK pathway, we found HO‐3867 induced cell apoptosis via the c‐Jun N‐terminal kinase (JNK)1/2 pathway. Our results suggest that HO‐3867 is an effective anticancer agent as its induction of cell apoptosis through JNK1/2 pathway in human oral cancer cells.